2014
DOI: 10.1002/zoo.21143
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the physiological and behavioral response of a male and female gorilla (Gorilla gorilla gorilla) during an introduction

Abstract: Prolonged stress responses can lead to infertility and death; therefore monitoring respective indicators like stress-related hormones and behaviors is an important tool in ensuring the health and well-being among zoo-housed animal populations. Changes in social structure, such as the introduction of a new conspecific, can be a source of stress. In April 2010, a sexually mature female western lowland gorilla (Gorilla gorilla gorilla) was brought to Lincoln Park Zoo (LPZ; Chicago, IL) from the Chicago Zoological… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
11
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 53 publications
(67 reference statements)
2
11
0
Order By: Relevance
“…Males excreted lower levels than females, replicating results from a study in captive animals involving one adult male and one female western lowland gorilla (Jacobs et al ., 2014). There are three potential explanations for this difference.…”
Section: Discussionsupporting
confidence: 82%
See 4 more Smart Citations
“…Males excreted lower levels than females, replicating results from a study in captive animals involving one adult male and one female western lowland gorilla (Jacobs et al ., 2014). There are three potential explanations for this difference.…”
Section: Discussionsupporting
confidence: 82%
“…This elevation is comparable to FGM analysis from captive western lowland gorillas following adrenocorticotrophic hormone challenge tests (Heistermann et al ., 2006; Nizeyi et al ., 2011a; Shutt et al ., 2012) and transportation between zoos for breeding purposes (e.g. an adult female showed a 7.6-fold increase in FGM; Jacobs et al ., 2014). Individual FGM profiles before and after inter-unit interactions showed that elevated FGM concentrations can quickly drop towards pre-event levels, implying that intensive faecal collection, especially around day 3 post-event, is crucial to assess the magnitude of any stressor.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations